Vers un outil de restauration du sensible, le motif ambiant en trois temps caractérisation, expérimentation, mise en projet. - Ammar Toumadher (VertigO)
This article is part of the desire to question the urban future from the point of view of a so-called sensitive ecology. In fact, we are trying to develop an operational specimen in terms of characterization and project implementation that takes into account all aspects of the environment, whether it is built or not. We also try to evaluate the operational scope of the atmosphere in terms of quality and sustainability of urban environments or how to safeguard the authenticity of the atmospheres of a place while projecting it into the future through the development of this tool. We have tried, through the «ambient patterns», to advance a working modality that goes through the logics of characterization as well as of projection of the atmospheres while involving the environmental data. We applied it in three different situations. One was in situ, one was in vitro, and the third was in utero. The first stage is mainly based on the objective of characterizing the sensitive experience. The second is in the middle of the characterization and the projection of the atmospheres and the last is in the order of the conceptualization and the project setting configured in the form of an intersectoral pedagogical experience. We had as study cases the neighborhoods of Capaci Piccolo and Capaci Grandi in Sousse. These districts were born around the beginnings of the French protectorate and proliferated until the 1960s due to the various waves of mainly Sicilian immigration. From independence (1956) the social fabric began to change. Today the neighborhoods are exclusively inhabited by Tunisians, while at the beginning several cultures and nationalities lived there.